Disaster Risk Reduction Management Awareness and Practices of Universal Banks in Bacolod City - Crendellee G. Cordevilla; Zeaphard Gerhart V. Caelian (Philippine Social Science Journal, 2020)
Disasters occur worldwide that affect many people and cause loss of life and destruction. The Philippines is considered one of the most frequently affected by natural calamities. It is also the third most disaster-prone country that costs billions of losses in the economy. Typhoon Haiyan, or the Super Typhoon Yolanda, one of the disastrous and strongest storms ever hit the country, brought massive destruction and casualties in the Philippines. Banks were also greatly affected during that time. This research focused on the extent of implementation of the Disaster Risk Reduction Management (DRRM) practices and the level of awareness of the bank employees of the universal banks in Bacolod City. It will contribute knowledge about Disaster Risk Reduction Management, especially on banks, and fill the literature gap. It aimed to determine whether there is a significant difference in the level of awareness of the employees and the extent of DRRM practices of the bank and whether there is a significant relationship between the two.